Thermoluminesce and Magnetical Susceptibility Applied to Paleoclimatic Reconstruction of the Taquaruçu Region ( Center-Eastern Brazil), During the Holocene - DOI 10.5216/bgg.v19i1.15297 - V.M. S, Kramer; J.C, Stevaux (Boletim Goiano de Geografia, 2011)
.